Harmonisasi Polarisasi Politik Masyarakat Pasca Pemilu 2024 Dan Implikasinya Terhadap Ketahanan Daerah Di Kota Surakarta - Shofa, Abd. Mu’id Aris; Alfaqi, Mifdal Zusron; Habibi, M. Mujtaba; Fattah , Zulfikar W; Ramli, Ahmad Faizuddin; Widiatmaka, Pipit (Jurnal Civic Hukum, 2024)
The purpose of this study is to find out (1) strategies for overcoming political polarization that occurs in Surakarta City after the 2024 Elections, (2) obstacles in overcoming political polarization in the people of Surakarta City after the 2024 Elections, and (3) its implications for regional resilience in Surakarta City. This study uses a qualitative approach with a descriptive research method, data collection techniques using in-depth interviews, observations, and documentation, and the data analysis used is interactive. The object of this research is related to the polarization of society after the election and regional resilience in the city of Surakarta. The results of the study show that the harmonization of political polarization carried out by the Surakarta city government in collaboration with all levels of society through dialogue activities, socialization, regular meetings of the village government with the community, heads of RT and RW, cooperation and recitation. However, in the harmonization, it turns out that there are obstacles, namely the existence of irresponsible individuals who provoke the community and there are still some people who are indirectly in conflict because they are hurt because their choice in the 2024 election is not elected. This harmonization has implications for regional resilience in the city of Surakarta which is increasingly resilient because the existence of Pancasila as an ideology can be maintained, the people of Surakarta are increasingly mature in democracy, the regional economy is increasing, socio-cultural life is more harmonious because prioritizing tolerance and security can be well maintained.